A Novel Image Analysis Approach Reveals a Role for Complement Receptors 1 and 2 in Follicular Dendritic Cell Organization in Germinal Centers - Anania, Jessica C.; Westin, Annika; Adler, Jeremy; Heyman, Birgitta (Frontiers in Immunology, 2021)
Follicular dendritic cells (FDCs) are rare and enigmatic cells that mainly reside in germinal centers (GCs). They are capable of capturing immune complexes, via their Fc (FcRs) and complement receptors (CRs) and storing them for long periods in non-degradative vesicles. Presentation of ICs on FDCs to B cells is believed to drive affinity maturation. CR1 and CR2 are expressed on B cells and FDCs. Cr2 knock out (KO) mice, lacking both receptors, have impaired antibody and GC responses. Utilizing novel ImageJ macro to analyze confocal fluorescence microscopy images of spleen sections, we here investigate how FDCs in wild type (WT) and Cr2 KO mice behave during the first two weeks after immunization with sheep red blood cells (SRBC). Mice were immunized with SRBC i.v. and spleen and serum samples harvested at various time points. As expected, antibody and GC responses in Cr2 KO mice were impaired in comparison to WT mice. Fewer FDCs were identified in Cr2 KO mice, and these exhibited differential localization and organization in comparison to WT mice. WT FDCs were primarily located within GCs at the light zone/dark zone border. FDCs from WT but not Cr2 KO mice were actively dispersed in GCs, i.e. tended to move away from each other, presumably to increase their surface area for B cell interaction. FDCs from Cr2 KO mice were more often found in follicles outside of the GCs and those within the GCs were closer to the periphery in comparison to WT FDCs. Expression of CR1 and CR2, FcγRIIB, and FcµR increased in FDCs from WT mice during the course of immunization. The results suggest that decreased ability to capture ICs by FDCs lacking CR1 and CR2 may not be the only explanation for the impaired GC and antibody responses in Cr2 KO mice. Poor FDC organization in GCs and failure to increase receptor expression after immunization may further contribute to the inefficient immune responses observed.